Endovaskular Repair pada Isolated Stabil Ruptur Aneurisma Arteri Iliaka : Sebuah Laporan Kasus Langka - Lalu Fahril Ilham; Sanditias Putrawan; I Made Arya Winata; Arif Zuhan; I Komang Yose Antara; Muhammad Farizka Firdaus; Mervin Arifianto Manginte (Lombok Medical Journal, 2024)
An iliac aneurysm is a bulging and weakness in the wall of the iliac artery, a group of arteries located in the pelvis. The development of the disease is not progressive and the diagnosis is often accidental. In some cases, the diagnosis is made after complications occur, the most serious of which is aneurysm rupture. Intervention for a ruptured aneurysm can cause total circulatory collapse and has a high risk of perioperative morbidity and mortality â‰¤50%. The incidence of this case is around 0.4% of all abdominal aneurysms. This case is a challenge to handle because the anatomical location and surgical procedure are considered difficult. Open surgery and endovascular intervention are the definitive therapies for iliac artery aneurysms.